Analisis Pemikiran Pendidikan Kritis Perspektif Ibnu Thufail - Labib Ulinnuha; Tejo Waskito; Yulita Putri (Bustanul Ulum Journal of Islamic Education, 2024)
This study aims to find the construction of critical education contained in the novel "Hayy Ibn Yaqzan" by Ibnu Thufail in relation to monotheism education. The novel "Hayy Ibn Yaqzan" is closely related to critical education because it contains the story of the spiritual and intellectual journey of humans in the search for truth. The background of this study is based on the interest in building the conception of critical educational reasoning and exploring other probabilities contained in the classic novel. The main sources of the study are the novel “Hayy Ibn Yaqzan" and related literature that is relevant to the research theme. The research method used is the library research method with content analysis techniques. The content analysis process is carried out by identifying and analyzing the construction of educational reasoning that appears in the novel, as in the findings of this study which include several important aspects, such as education through observation of nature, the use of reason and rational reasoning in understanding religion, encouraging independence in learning religion, moral and ethical education, and the importance of dialogue and critical reflection in the search for spiritual understanding. This study provides new insights for the development of a critical educational approach in the context of Islamic education, as well as enriching the relationship between Islamic literature and critical education. The results of this study can be a reference for Islamic education practitioners in developing critical, reflective, and contextual educational strategies and approaches, especially in relation to the actualization of the independent curriculum.